2015
DOI: 10.1007/s10895-015-1566-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Glucose and Cholesterol Using a Novel Optimized Luminol- CuO Nanoparticles-H2O2 Chemiluminescence Method by Box–Behnken Design

Abstract: In this study, a simple, rapid and sensitive luminol-CuO nanoparticles-H2O2 chemiluminescence (CL) method has been proposed for determination of glucose and cholesterol in plasma. Response surface methodology (RSM) based on Box-Behnken design (BBD) was used to optimize the most important operating variables (solution pH effect and the CL reagents concentration) of luminol CL system. In optimum conditions, it was found that CuO nanoparticles (NPs) could enhance the CL intensity and the method sensitivity toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It was reported that H 2 O 2 decomposition on supported metal catalysts such as Au NPs, Ag NPs and CuO NPs involved the formation of hydroxyl radicals OHc. [40][41][42] In the same manner, we suggested that the O-O bond of H 2 O 2 might be broken up into double OHc radicals by virtue of the catalysis of Au nanoclusters. The OHc reacted with cSO 3 À to form HSO 4…”
Section: Possible Mechanism Of CL Systemmentioning
confidence: 68%
“…It was reported that H 2 O 2 decomposition on supported metal catalysts such as Au NPs, Ag NPs and CuO NPs involved the formation of hydroxyl radicals OHc. [40][41][42] In the same manner, we suggested that the O-O bond of H 2 O 2 might be broken up into double OHc radicals by virtue of the catalysis of Au nanoclusters. The OHc reacted with cSO 3 À to form HSO 4…”
Section: Possible Mechanism Of CL Systemmentioning
confidence: 68%
“…25,26 The application realm of the system was then further expanded by other researchers. [27][28][29][30][31][32] However, to the best of our knowledge, the oxidase-like activity of CuO NPs, a discovered 33 but less known property of CuO NPs, has somehow been neglected and has not yet been incorporated in analytical applications. It should be noted that the oxidase-like activity of V 2 O 5 nanowires 34 and CoFe 2 O 4 NPs 35 toward the luminol-O 2 CL reaction has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Wang et al decreased the H 2 O 2 detection limit of the luminol reaction via the synthesis and use of a hemin and poly(ethylene glycol) methyl ether catalyst [36]. The new catalyst resulted in a detection limit of 1.8 nM [36], lower than other luminol-H 2 O 2 detection levels [31,36,[43][44][45].…”
Section: Developments From 2015 To 2019mentioning
confidence: 99%